Analisis Yuridis Pertanggungjawaban Pidana Pelaku Cyberbullying di Kalangan Remaja Berdasarkan UU ITE - Maskadi Maskadi; Aturkian Laia (INDO PUBLISHING, 2026)
Technological advancements increase the risk of adolescent cyberbullying. This complex phenomenon arises because both perpetrators and victims are generally minors. This normative juridical research analyzes cyberbullying regulations, adolescent criminal liability, juvenile justice system law (UU SPPA) implementation, victim protection, and law enforcement obstacles. Results show cyberbullying is not regulated as a distinct offense, but its elements are scattered across provisions regarding defamation, threats, extortion, and hate speech. Criminal liability remains possible for adolescents, but its application must comply with restorative justice and rehabilitation principles under UU SPPA. Conversely, victim protection is still hindered by digital evidence, low legal literacy, informal settlements, and suboptimal inter-agency coordination. Therefore, adolescent cyberbullying enforcement requires a balanced model harmonizing victim protection, juvenile perpetrator rehabilitation, and legal certainty in Indonesia's digital space.